👤
a fost răspuns

rezolvati ecuatiile (x-7)/2013+(x-3)/2017=(x-2013)/7+(x-2017)/3

Răspuns :

[tex]\frac{x-7}{2013}+\frac{x-3}{2017}=\frac{x-2013}{7}+\frac{x-2017}{3}\\\\ \frac{x-2020+2013}{2013}+\frac{x-2020+2017}{2017}=\frac{x-2020+7}{7}+\frac{x-2020+3}{3}\\\\ \frac{x-2020}{2013}+\frac{2013}{2013}+\frac{x-2020}{2017}+\frac{2017}{2017}=\frac{x-2020}{7}+\frac{7}{7}+\frac{x-2020}{3}+\frac{3}{3}\\\\ \frac{x-2020}{2013}+1+\frac{x-2020}{2017}+1=\frac{x-2020}{7}+1+\frac{x-2020}{3}+1\\\\ \frac{x-2020}{2013}+\frac{x-2020}{2017}=\frac{x-2020}{7}+\frac{x-2020}{3}\\
\\  \frac{x-2020}{7}+\frac{x-2020}{3}-\frac{x-2020}{2013}-\frac{x-2020}{2017}=0\\
\\ (x-2020)(\frac{1}{7}+\frac{1}{3}-\frac{1}{2013}-\frac{1}{2017})=0~(1)\\\\ \\\\ \frac{1}{7}>\frac{1}{2013}\\\\ \frac{1}{3}>\frac{1}{2017}\\\\ \Rightarrow \frac{1}{7}+\frac{1}{3}>\frac{1}{2013}+\frac{1}{2017}\\\\ \Rightarrow \frac{1}{7}+\frac{1}{3}-\frac{1}{2013}-\frac{1}{2017}>0~(2)\\\\Din~(1)~si~(2)\Rightarrow x-2020=0\\ \\ \Rightarrow x=2020\\\\ S=\{2020\} [/tex]